Development and field evaluation of near-isogenic lines of GR2-EBRRI dhan29 golden rice - Biswas, Partha S.; Swamy, B.P. Mallikarjuna; Kader, Md. Abdul; Hossain, Md. Alamgir; Boncodin, Raul; Samia, Mercy; Hassan, Md. Lutful; Wazuddin, M.; MacKenzie, Donald; Reinke, Russell (Frontiers Media, 2021)
Vitamin A deficiency remains a common public health problem among the rice-dependent poor people in the developing countries of Asia. Conventional milled rice does not contain provitamin A (β-carotene) in is edible part (endosperm) and is also deficient in essential minerals, such as iron and zinc. Transgenic Golden Rice event GR2E, which produces β-carotene in its endosperm, was used as a parent to introgress the transgene locus conferring β-carotene biosynthesis into a widely grown rice variety, BRRI dhan29, which covers around 26.1% of the irrigated rice area (4.901 Mha) of Bangladesh in the dry season. The current study reports the introgression process and field performance of GR2E BRRI dhan29 Golden Rice. The background recovery of GR2E BRRI dhan29 lines at BC5F2 generation was more than 98% with a 6K SNP-chip set. The transgenic GR2E BRRI dhan29 yielded 6.2 t/ha to 7.7 t/ha with an average of 7.0 ± 0.38 t/ha, while the non-transgenic BRRI dhan29 yielded 7.0 t/ha under confined field conditions in Bangladesh. Moreover, no significant difference between GR2-E BRRI dhan29 Golden Rice and non-transgenic BRRI dhan29 in any measured trait was observed in the multi-location trials conducted at five locations across the country. Furthermore, the appearance of cooked and uncooked rice was similar to that of BRRI dhan29 except for the yellow color indicating the presence of carotenoids. Total carotenoid content in the selected introgression lines ranged from 8.5 to 12.5 μg/g with an average of 10.6 ± 1.16 μg/g. This amount is sufficient to deliver approximately 66 and 80% of the recommended daily intake of vitamin A for children and women, respectively, assuming complete substitution of white rice in the diet with Golden Rice. However, the lead selected line(s) need further evaluation at open field conditions before deciding for commercial cultivation. A large-scale feeding trial among the malnourished community with this newly developed GR2-E BRRI dhan29 Golden Rice is also required to validate its efficacy in alleviating vitamin A deficiency.